Akselerometer dan Giroskop MEMs: Aplikasi dalam Sensor Seismik Elektrokimia - Yusuf Hotdes Triwan Situngkir; Risnu Irviandi (Journal of Computation Physics and Earth Science (JoCPES), 2022)
This journal is intended to provide an initial overview or introduction to an electrochemical seismic sensor device assisted with vibration detection features using a liquid resistance mass. This research introduces the first electrochemical seismic sensor that uses a liquid resistance mass (electrolyte solution) as a detecting element to convert environmental vibrations into active ion imbalances between electrodes, resulting in an electric current output. This paper will describe the use of MEMs in motion or vibration (seismic) analysis, validating the validity of concepts that have been widely fabricated, ranging from the use of conventional electrodes to earthquake detection and recording. In addition, this study discusses the operating principle, sensing mechanism, and applications of MEMS- based accelerometer and gyroscope sensors, where accelerometers measure linear acceleration and gyroscopes detect angular motion due to Coriolis acceleration. The comparative analysis shows the important role of MEMS sensors in various fields, such as shipping, aerospace, robotics and smart devices, and reveals the efficiency of MEMS-based electrochemical seismic sensors in earthquake monitoring with lower power and fabrication costs. This research opens up opportunities for the development of MEMS-based seismometers for environmental and geological monitoring applications, with recommendations for continued research for optimization of electrochemical materials and system integration to improve overall seismic response.